Evaluation of Soil Biodiversity in Alpine Habitats through eDNA Metabarcoding and Relationships with Environmental Features - Noemi Rota (Forests, 2020)
Soil biodiversity is fundamental for ecosystems, ensuring many ecosystem functions, such as nutrient cycling, organic matter decomposition, soil formation, and organic carbon pool increase. Due to these roles, there is a need to study and completely understand how soil biodiversity is composed through different habitats. The aim of this study was to describe the edaphic soil community of the alpine environments belonging to the Gran Paradiso National Park, thus detecting if there are any correlation with environmental features. We studied soil fauna through environmental DNA metabarcoding. From eDNA metabarcoding, 18 families of arthropods were successfully detected, and their abundance expressed in terms of the relative frequency of sequences. Soil faunal communities of mixed coniferous forests were characterized by Isotomidae, Entomobriydae, Hypogastruridae, and Onychiuridae; while mixed deciduous forests were composed mostly by Isotomidae, Cicadidae, Culicidae, and Neelidae. Calcicolous and acidic grasslands also presented families that were not detected in forest habitats, in particular Scarabaeidae, Curculionidae, Brachyceridae, and had in general a more differentiated soil community. Results of the Canonical Component Analysis revealed that the main environmental features affecting soil community for forests were related to vegetation (mixed deciduous forests, tree basal area, tree biomass, Shannon index), soil (organic layers and organic carbon stock), and site (altitude); while for prairies, soil pH and slope were also significant in explaining soil community composition. This study provided a description of the soil fauna of alpine habitats and resulted in a description of community composition per habitat and the relation with the characteristic of vegetation, soil, and topographic features of the study area. Further studies are needed to clarify ecological roles and needs of these families and their role in ecosystem functioning.